3D modeling of interior spaces : learning the language of indoor architecture :Powerpoint - Díaz-Vilariño, L. (University of Twente, 2020)
This lecture presents: Need for 3d indoor models; 3d indoor modeling: the challenge Indoor architectural design; Palladian grammar (simplified); A shape grammar for indoor modeling; Learning grammar rules from a point cloud; Separability of walls and empty spaces.